Potensi Wisata Kuliner di Rest Area dengan Strategi Analisis Menu di Kukm Rest Area 379A, 389B, dan 391A - Cindy Citya Dima (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The role of academics is urgently needed in strengthening human resources for owners and employees who run businesses and provide information on online sales and take away as well as drive-thru which use cashless payments as an alternative to increasing sales turnover in the midst of the Covid 19 Pandemic situation. The method used is qualitative or descriptive. with a phenomenological approach with data triangulation (method: in-depth interviews and observations at 30 tenant in the three rest areas, between researchers: culinary and tourism management, data sources: documentation and other document references). The results obtained are that the potential for culinary tourism in the Rest Area is a change in the lifestyle of tourists to find regional specialities in a rest area in addition to supporting facilities in the rest area that create a market share rest area, structured financial administration based on a menu management approach, developing delicious, attractive, and hygienic product variants and increasing the mastery of information technology for product marketing that is integrated with non-cash payments